Cross-cultural design. methods, tools, and users : 10th International Conference, CCD 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: methods, tools, and users : 10th International Conference, CCD 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available